(untitled) (Research, Society and Development, 2021)
The literature provides a variety of methodological tools for analyzing data collected in a qualitative research with an educational bias. Among the existing proposals we find the method called thematization or thematic analysis, which aims to organize the data collected from the research in a way that allows the best treatment of the findings found in the research, it is worth mentioning that these data are collected through interviews, written materials and oral testimonies. In this way, thematization is a tool that can help systematize the collected material and enable the reader to have a rich and articulate reading. In view of this, this article aims to present a case study, in which thematic analysis was used in the data collected during the delivery of a training course for science teachers in the final years of elementary school, in the cities of Três Rios and Paraíba do Sul (municipalities in the interior of the State of Rio de Janeiro), whose theme was “Workshop of recreational activities for the teaching of Microbiology in Elementary Education”. In this perspective, the work showed that, given the complexity of information collected during the training course, thematization was an instrument that enabled greater reflection and articulation with the theory.